In-Pipe Electrical Machine Design for Smart Clean Water Grid Monitoring and Control Stations - Erkan, Murat; Boynuegri, Ali Rifat; Tekgun, Burak (IEEE, 2025)
This study presents the design of an electric machine intended to supply the electrical energy required for the operation of electronic devices and mechanical equipment that form part of a clean water smart grid network powered by renewable energy sources. The proposed machine is a permanent magnet synchronous generator (PMSG), specifically designed to operate under realistic physical and hydraulic conditions within clean water distribution infrastructure. The in-pipe turbine responsible for driving the rotor of the generator was selected based on findings from a symposium paper identified through a comprehensive literature review. The daily energy requirements of the smart grid's electronic and industrial mechanical components were both theoretically estimated and experimentally validated, leading to the selection of a suitable energy storage unit. Pressure data from the clean water distribution line located on the street of the design office was measured and recorded at one second intervals over a 24-hour period. Using this dataset, the optimal hydraulic conditions and time frame for battery charging were identified from the pressure-time profile. A representative duty cycle was then defined, and the performance analysis of the in-pipe permanent magnet synchronous generator was carried out accordingly.
Keywords: In-Pipe Energy; Smart Grid; Renewable Energy; Permanent Magnet Synchronous Generator; Energy & Fuels; Engineering; Telecommunications